Attitude towards vaccination among health science students before the COVID-19 pandemic - Pérez-Rivas, Francisco Javier (2021)
Health science students are tomorrow's health professionals, the duties of whom could include vaccination. This work examines the general attitude towards vaccination in students attending the Faculty of Nursing, Physiotherapy and Chiropody at a university in Madrid, Spain, using the 'Attitudes and Behaviour With Regard To Vaccination Among Health Science Students Questionnaire'. The results were subjected to multivariate analysis to identify the influence of sex, the degree being pursued, and 'course year'. The number of students vaccinated against influenza in the campaign preceding the present study was also recorded, as were the factors that influenced decision-making in this regard. A total of 934 students completed the questionnaire. Their beliefs regarding vaccination were positive (mean score 3.23 points out of 4), as was their behaviour (3.35/4). Their general attitude (all variables taken together) was therefore also good (3.27/4). Only 26.8% of the students had been vaccinated against influenza. Beliefs scores among the students of nursing in their more senior course years were significantly better than those recorded for all other groups. These students also showed the best general attitude towards vaccination and formed the largest group vaccinated against influenza. The results obtained are encouraging since nursing students are the most likely of future healthcare professionals to be involved in vaccination programmes.